Odpowiedzi

2010-02-15T20:59:17+01:00
1)
2x + y = 9
5x - 4y = 3

y = 9 -2x
5x - 4(9- 2x) = 3

y = 9 - 2x
5x - 36 + 8 x = 3

y= 9 - 2x
5x +8x = 3 +36

y = 9 - 2x
13x = 39 \ 13
x = 3

2)
4x - 5y = -4
-2x + 3y - 1,1

4x - 5y = 4
-2x +3y = 1,1 \*2

4x - 5y =4
-4x +6y = 2,2
y= 6,2

4x - 5 * 6,2 =4
4x - 31 = 4
4x = 4 + 31
4x = 34 \4
x = 8,5





2010-02-15T20:59:47+01:00
[2x+y=9
[5x-4y=3

2x=9-y
2,5(9-y)-4y=3

2x=9-y
22,5-2,5y-4y=3

2x=9-y
-6,5y=-19,5

2x=9-y
y=3

2x=9-3
y=3

2x=6
y=3

x=3
y=3


[-2x+3y=1,1
[4x-5y=-4

-2x=1,1+3y
4x-5y=-4

2x=-1,1+3y
2(-1,1+3y)-5y=-4

2x=-1,1+3y
-2,2+6y-5y=-4

2x=-1,1+3y
y=-1,8

2x=-1,1-5,4
y=-1,8

2x=-6,5
y=-1,8

x=-3,25
y=-1,8